Representasi Hijab Voal Syar’i pada Akun Instagram @merajutkisah - Sri Arnita; Gun Gun Heryanto; Tantan Hermansah; Muhammad Fanshoby (Universitas Islam Negeri Madura, 2024)
The phenomenon of using the hijab from year to year is increasingly diverse. However, not only are there more and more uses and models, but the motifs on each hijab are also increasingly diverse. Merajut Kisah in this case presents a new face in the world of Muslim fashion where it gives a different touch to the hijab. Merajut Kisah adds a design inspired by various countries in the world that have a history of Islamic heritage and its development. This study aims to answer the question of how the syar'i voal hijab represents Merajut Kisah of Eyes of Andalucia in the series Andalusia, Granada, Alhambra, Seville, Plaza de Espana, and Cordoba. The theory used in this study is Stuart Hall's representation theory. Hall's representation has three important points in the analysis process, namely representational elements, representational systems, and representational approaches. The results of the study show that the six syar'i voal hijab of Merajut Kisah of Eyes of Andalucia represents the Islamic culture that once existed in Andalusia. The building, which was used as design inspiration by the Merajut Kisah team, is proven to implement the concept of art in Islam which combines geometry, calligraphy, and plant motifs. The science of geometry is used to create art combined with calligraphy to praise His greatness. Then, to beautify the two arts, plant motifs were also presented.